Poor Agreement Between Next-Generation DNA Sequencing and Bacterial Cultures in Orthopaedic Trauma Procedures. (16th March 2022) - Natoli, Roman M.; Marinos, Dimitrius P.; Montalvo, Ryan N.; Degani, Yasmin; Ochenjele, George; Griffith, Cullen; Ding, Anthony; Gitajn, I. Leah; Manson, Theodore T.; Johnson, Aaron J.; Kjellerup, Birthe Veno; Harro, Janette M.; et al.
Abstract : Background: Next-generation DNA sequencing (NGS) detects bacteria-specific DNA corresponding to the 16S ribosomal RNA gene and can identify bacterial presence with greater accuracy than traditional culture methods. The clinical relevance of these findings is unknown. The purpose of the present study was to compare the results from bacterial culture and NGS in order to characterize the potential use of NGS in orthopaedic trauma patients. Methods: A prospective cohort study was performed at a single academic, level-I trauma center. Three patient groups were enrolled: (1) patients undergoing surgical treatment of acute closed fractures (presumed to have no bacteria), (2) patients undergoing implant removal at the site of a healed fracture without infection, and (3) patients undergoing a first procedure for the treatment of a fracture nonunion who might or might not have subclinical infection. Surgical site tissue was sent for culture and NGS. The proportions of culture and NGS positivity were compared among the groups. The agreement between culture and NGS results was assessed with use of the Cohen kappa statistic. Results: Bacterial cultures were positive in 9 of 111 surgical sites (110 patients), whereas NGS was positive in 27 of 111 surgical sites (110 patients). Significantly more cases were positive on NGS as compared with culture (24% vs. 8.1%; p = 0.001), primarily in the acute closed fracture group. No difference was found in terms of the percent positivity of NGS when comparing the acute closed fracture, implant removal, and nonunion groups. With respect to bacterial identification, culture and NGS agreed in 73% of cases (κ = 0.051; 95% confidence interval, −0.12 to 0.22) indicating only slight agreement compared with expected chance agreement of 50%. Conclusions: NGS identified bacterial presence more frequently than culture, but with only slight agreement between culture and NGS. It is possible that the increased frequency of bacterial detection with molecular methods is reflective of biofilm presence on metal or colonization with nonpathogenic bacteria, as culture methods have selection pressure posed by restrictive, artificial growth conditions and there are low metabolic activity and replication rates of bacteria in biofilms. Our data suggest that NGS should not currently substitute for or complement conventional culture in orthopaedic trauma cases with low suspicion of infection. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.